2011 Statutes and Administrative Regulations of the Telecommunication Sector - Aranha, Marcio Iorio; Lima, João Alberto de Oliveira; Lira, Laura (Law, State and Telecommunications Review, 2012)
Statutes, regulations, administrative and judicial decisions applied to the telecommunications sector in Brasil in 2011.